Tnd Box Uno Stacko Media Development On Thematic Lessons - Lailatul Mufarrokhah; Yulia Pramusinta (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2022)
This research on the development of the TND Box Uno Stacko media is based on several things including (1) the lack of use of media to support the thematic learning process (2) lack of interest in learning, and students' learning motivation. In overcoming these problems, it is necessary to develop media in the form of developing TND Box Uno Stacko media. The study was conducted in class IV SDN Tanjung as many as 20 students. This research was conducted based on several objectives, namely (1) producing a product in the form of TND Box Uno Stacko media for fourth-grade students at SDN Tanjung, (2) knowing the level of attractiveness of the TND Box Uno Stacko media. This study uses the ADDIE development model. The results of the TND Box Uno Stacko validation are 98.6 media experts with very valid categories, 91.6 linguists (very valid) validation results, 87 material expert validation results (very valid), 91.9 user expert validation results (very valid). Field test results show the attractiveness rate reaches 99% (very interesting). So it was concluded that the TND Box Uno Stacko media was proven to be valid and interesting for fourth graders at SDN Tanjung.